2008
DOI: 10.1021/ja710207s
|View full text |Cite
|
Sign up to set email alerts
|

Studies on A New Biosynthetic Pathway for Menaquinone

Abstract: Menaquinone is biosynthesized from chorismate via a new pathway involving 1,4-dihydroxy-6-naphthoate in Streptomyces and presumably in pathogenic bacteria Helicobacter and Campylobacter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 16 publications
(45 reference statements)
2
46
0
Order By: Relevance
“…6 The 13 C-NMR spectrum of MK labeled with [U- 13 C 6 ]glucose showed a labeling pattern that could be explained by the incorporation of [U- 13 C 6 ]glucose into MK through the shikimate pathway by the condensation of phosphoenolpyruvate (PEP) and erythrose-4-phosphate (E4P). These two compounds used for A-ring formation were the same as those in the known pathway, but the incorporated positions (PEP into C-7 and -8, and E4P into C-8a, -4a, -5 and -6) differed from those in the known pathway ( Figure 1).…”
Section: Tracer Experiments Using [U-13 C]glucose and S Coelicolor Amentioning
confidence: 99%
See 1 more Smart Citation
“…6 The 13 C-NMR spectrum of MK labeled with [U- 13 C 6 ]glucose showed a labeling pattern that could be explained by the incorporation of [U- 13 C 6 ]glucose into MK through the shikimate pathway by the condensation of phosphoenolpyruvate (PEP) and erythrose-4-phosphate (E4P). These two compounds used for A-ring formation were the same as those in the known pathway, but the incorporated positions (PEP into C-7 and -8, and E4P into C-8a, -4a, -5 and -6) differed from those in the known pathway ( Figure 1).…”
Section: Tracer Experiments Using [U-13 C]glucose and S Coelicolor Amentioning
confidence: 99%
“…On the basis of bioinformatic screenings, gene knockouts, shotgun cloning with isolated mutants and in vitro studies with recombinant enzymes, we have deduced the outline of the alternative pathway. 6,7 In this review, I introduce this alternative pathway, which we designated as the futalosine pathway. 7 HOW IT STARTED I have been studying the enzymes and genes responsible for the biosyntheses of isoprenoids produced by actinomycetes.…”
Section: Introductionmentioning
confidence: 99%
“…In Escherichia coli, MK was shown to be derived from chorismate by eight enzymes, designated MenA-H. 1,2 However, we have revealed that an alternative pathway (we named it the futalosine pathway; Figure 1) [3][4][5] was operating in some microorganisms including Helicobacter pylori, which causes gastric carcinoma. As humans and some useful intestinal bacteria, such as lactobacilli, possess the classical pathway, and MK biosynthesis is essential for survival of microorganisms, 4 the futalosine pathway is an attractive target for the development of specific anti-H. pylori drugs.…”
mentioning
confidence: 99%
“…In Escherichia coli, MK was shown to derive from chorismate via a pathway involving eight enzymes, designated MenA-H (Figure 1a, canonical pathway). 1, 2 However, we revealed that an alternative pathway (Figure 1b, futalosine pathway) [3][4][5][6][7] was operating in some microorganisms including Helicobacter pylori, which causes gastric carcinoma. As humans and some useful intestinal bacteria, such as lactobacilli, possess the classical pathway, and MK biosynthesis is essential for the survival of microorganisms, the futalosine pathway is an attractive target for the development of specific anti-H. pylori drugs.…”
mentioning
confidence: 96%
“…To identify compounds that specifically inhibit the futalosine pathway, we employed a previously developed screening method. 8 For the initial screening, we used the paper disk method and employed two closely related Bacillus strains, Bacillus subtilis strain 168 and 3 Bacillus halodurans C-125, as the test organisms. By genome sequencing, these two strains had been shown to possess a high degree of similarity.…”
mentioning
confidence: 99%